A case of small bowel obstruction due to infection with Bolbosoma sp. (Acanthocephala: Polymorphidae). Issue 1 (February 2019) - Kaito, Shuko; Sasaki, Mizuki; Goto, Kentaro; Matsusue, Ryo; Koyama, Hiroshi; Nakao, Minoru; Hasegawa, Hideo
Abstract: A case of small bowel obstruction caused by Bolbosoma sp. infection is reported. A 27-year-old woman admitted with abdominal pain was diagnosed as small bowel obstruction. Laparoscopic surgery revealed induration in jejunum at ca. 120 cm distal to the ligament of Treiz, attributed to a band connecting the serosa to the ascending mesocolon. Resected band contained an acanthocephalan accompanying foreign body reaction with abscess formation. The parasite belonged to the genus Bolbosoma, of which identification was made by DNA sequence analysis. This is the eighth case of Bolbosoma infection in humans, and the first one causing an ileus. Graphical abstract: Highlights: Eighth human case of Bolbosoma infection. First case causing ileus. Identified based on DNA sequencing.